2012
DOI: 10.1038/embor.2011.260
|View full text |Cite
|
Sign up to set email alerts
|

Loss of autophagy in hypothalamic POMC neurons impairs lipolysis

Abstract: Autophagy degrades cytoplasmic contents to achieve cellular homeostasis. We show that selective loss of autophagy in hypothalamic proopiomelanocortin (POMC) neurons decreases a-melanocyte-stimulating hormone (MSH) levels, promoting adiposity, impairing lipolysis and altering glucose homeostasis. Ageing reduces hypothalamic autophagy and a-MSH levels, and aged-mice phenocopy, the adiposity and lipolytic defect observed in POMC neuron autophagy-null mice. Intraperitoneal isoproterenol restores lipolysis in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 19 publications
8
170
2
Order By: Relevance
“…This suggests that alterations in autophagic activity can modulate inter-organ crosstalk, a notion also supported by the observation of impaired lipolysis when autophagy was genetically disrupted in hypothalamic pro-opiomelanocortin (POMC) neurons [24].…”
Section: The Role Of Autophagy In Adipose Dysfunction and Inflammationmentioning
confidence: 85%
See 1 more Smart Citation
“…This suggests that alterations in autophagic activity can modulate inter-organ crosstalk, a notion also supported by the observation of impaired lipolysis when autophagy was genetically disrupted in hypothalamic pro-opiomelanocortin (POMC) neurons [24].…”
Section: The Role Of Autophagy In Adipose Dysfunction and Inflammationmentioning
confidence: 85%
“…Interestingly, hypothalamic inhibition of autophagy using ATG7 siRNA-mediated knockdown resulted in increased energy consumption and reduced energy expenditure, leading to impaired adipose lipolysis, exacerbation of obesity and whole-body insulin resistance in response to HFD feeding [24,52].…”
Section: Effects Of Dysregulated Autophagy In the Hypothalamus On Obementioning
confidence: 99%
“…Autophagy knockout in adipose tissue also leads to protection from diet-induced obesity and insulin resistance together with impaired adipocyte differentiation 7,9 . Autophagy deficiency in hypothalamic proopiomelanocortin neurons leads to obesity and glucose intolerance [47][48][49] . In addition to the location of autophagy deficiency, severity of autophagy deficiency could also be important.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has also been examined in another nutrient-sensing hypothalamic neuron, the proopiomelanocorti n (POMC) neuron, which produces anorexigenic neuropeptides that inhibit food intake and promote energy expenditure 87 . Multiple studies have demonstrated that Atg7 deletion in POMC neurons causes increased body weight owing to hyperphagia [87][88][89] .…”
Section: Danon Diseasementioning
confidence: 99%
“…Multiple studies have demonstrated that Atg7 deletion in POMC neurons causes increased body weight owing to hyperphagia [87][88][89] . However, more recent research argues against a general role for POMC neuron-specific autophagy in the control of energy homeostasis.…”
Section: Danon Diseasementioning
confidence: 99%